Androgen production and action in the ovary. (June 2021) - Franks, Stephen
Abstract: Androgen production by the ovary fulfils an essential physiological role, not only in providing substrate for oestrogen production but also by playing an important part in the normal growth and maturation of the ovarian follicle. Excess androgen production is a cardinal feature of polycystic ovary syndrome, a major cause of ovulatory and metabolic dysfunction in women. This review focuses on recent data that shed light on the molecular and cellular mechanisms involved in both normal and excess androgen production. It also includes a summary of recent advances in understanding the impact of androgens on ovarian function in normal and polycystic ovaries.